Mapping the landscape of biology learning media publications in Indonesia: A bibliometric analysis - Dian Pratiwi; Sri Rahayu Lestari; Susriyati Mahanal (Universitas Papua, 2026)
Media integration in biology education is increasingly emphasized to support active, meaningful, and student-centered learning. This bibliometric analysis aims to explore trends, patterns, and research focus areas on media use in biology learning over the past ten years. This study employed a Scopus search using the keywords